How Costly are Labor Gender Gaps? : Estimates for the Balkans and Turkey - Cuberes, David; Teignier, Marc (World Bank, Washington, DC, 2015)
In this paper, survey data are used to document the presence of gender gaps in self-employment, employership, and labor force participation in seven Balkan countries and Turkey. The paper examines the quantitative effects of the gender gaps on aggregate productivity and income per capita in these countries. In the model used to carry out this calculation, agents choose between being workers, self-employed, or employers, and women face several restrictions in the labor market. The data display very large gaps in labor force participation and in the percentage of employers and self-employed in the labor force. In almost all cases, these gaps reveal a clear underrepresentation of women. The calculations show that, on average, the loss associated with these gaps is about 17 percent of income per capita. One-third of this loss is due to distortions in the choice of occupations between men and women. The remaining two-thirds corresponds to the costs associated with gaps in labor force participation. The dimensions of these gender gaps and their associated costs vary considerably across age groups, with the age bracket 36–50 years being responsible for most of the losses.